On the relation between architectural smells and source code changes. Issue 1 (27th October 2021) - Sas, Darius; Avgeriou, Paris; Pigazzini, Ilaria; Arcelli Fontana, Francesca
Abstract: Although architectural smells are one of the most studied type of architectural technical debt, their impact on maintenance effort has not been thoroughly investigated. Studying this impact would help to understand how much technical debt interest is being paid due to the existence of architecture smells and how this interest can be calculated. This work is a first attempt to address this issue by investigating the relation between architecture smells and source code changes. Specifically, we study whether the frequency and size of changes are correlated with the presence of a selected set of architectural smells. We detect architectural smells using the Arcan tool, which detects architectural smells by building a dependency graph of the system analyzed and then looking for the typical structures of the architectural smells. The findings, based on a case study of 31 open‐source Java systems, show that 87% of the analyzed commits present more changes in artifacts with at least one smell, and the likelihood of changing increases with the number of smells. Moreover, there is also evidence to confirm that change frequency increases after the introduction of a smell and that the size of changes is also larger in smelly artifacts. These findings hold true especially in Medium–Large and Large artifacts. Abstract : Allegedly, architectural smells (ASs) increase the effort necessary for developers to efficiently maintain and evolve their software. In this work, we mine, from over 30 Java projects and their software repositories, the AS affecting the projects and how source code files changed over time. Findings show that the presence of an AS in a software artifact correlates with an increased code churn and change frequency in the smelly files in contrast to non‐smelly files.